Transfection of pulmonary cells by stable pDNA-polycationic hybrid nanostructured particles. (30th January 2019) - Gaspar, Diana P; Vital, Joana; Leiva, María C; Gonçalves, Lídia MD; Taboada, Pablo; Remuñán-López, Carmen; Vítor, Jorge; Almeida, António J
Aim: Cationically modified solid lipid nanoparticles (SLN) were investigated as plasmid DNA ( pDNA ) carriers and transfection agents for the pulmonary route.Materials & methods: pDNA -loaded SLN were produced using glyceryl dibehenate or tristearate as matrix lipids and chitosan as surface charge modifier, and encapsulated by spray-drying in mannitol and trehalose microspheres.Results: Nanoparticles of 200 nm, and zeta potential around +15 mV were produced. Electrophorectic analysis confirmed plasmid stability and integrity. The pDNA -loaded SLN were able to transfect the Calu-3 and A549 pulmonary cell lines, while showing low cytotoxicity. Microencapsulation of SLN yielded dry powders suitable for inhalation that protected pDNA from degradation.Conclusion: Microencapsulated SLN are a promising safe and effective carrier system for pulmonary gene delivery following pulmonary administration.